2005
DOI: 10.1088/0953-8984/17/21/020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin antiferromagnetic films on a ferromagnetic substrate: a first-principles study of Mn on Fe(001)

Abstract: The electronic and magnetic structures of Mn films with thicknesses of up to 12 monolayers on Fe(001) are investigated by means of first-principles calculations, with a focus on the thicker films. The Mn films show an in-layer antiferromagnetic structure and couple antiferromagnetically to the Fe substrate. The magnetic moments at the Mn surface and at the Mn-Fe interface are significantly enhanced, as compared to the respective bulk values. Several surface states are found at the centre of the two-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The two major magnetic configurations parallel ͑P͒ and antiparallel ͑AP͒ are defined in terms of the Fe-electrode magnetizations. As was shown recently by first-principles electronic-structure calculations, 13 Mn couples LAFM with respect to the Fe͑001͒ substrate, provided the Mn film is sufficiently thick ͑Ͼ7 ML͒. These findings are consistent with experimental observations.…”
supporting
confidence: 91%
“…The two major magnetic configurations parallel ͑P͒ and antiparallel ͑AP͒ are defined in terms of the Fe-electrode magnetizations. As was shown recently by first-principles electronic-structure calculations, 13 Mn couples LAFM with respect to the Fe͑001͒ substrate, provided the Mn film is sufficiently thick ͑Ͼ7 ML͒. These findings are consistent with experimental observations.…”
supporting
confidence: 91%
“…For instance, in the experiments of Yamada et al [19] and Schlickum et al [20] only the p(1 × 1) configuration at the surface is found, but there are some theoretical studies in which antiferromagnetic c(2 × 2) configurations are proposed [22]. Concerning the magnetic coupling at the Mn/Fe interface, some theoretical studies found this coupling to be ferromagnetic [21,22], while other studies proposed an antiferromagnetic coupling [23]. This makes this system particularly interesting as regards the possibility of noncollinear magnetism and its response to external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…One of the systems intensively investigated experimentally [19,20] as well as theoretically [21][22][23] is Mn supported on Fe. The fact that Mn is located in the periodic table between Fe (ferromagnetic) and Cr (antiferromagnetic) gives rise to a large variety of local magnetic couplings in the collinear framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of band gaps are more or less equal to that calculated by GGA method. We are still working to reproduce exact band gaps in these systems by using other methods like multiple scattering technique [20].…”
Section: Discussionmentioning
confidence: 99%